2021
DOI: 10.7759/cureus.14141
|View full text |Cite
|
Sign up to set email alerts
|

Staff Awareness of Anti-Cholinergic Burden (ACB) - A Qualitative Cross-Sectional Study in a Tertiary Care Hospital

Abstract: Introduction and hypothesis Anticholinergics are commonly used for a variety of conditions including urinary incontinence. Many studies show the ill effects of anticholinergics on cognition resulting in increased morbidity and mortality. However, the interaction of anticholinergic medications and cumulative anti-cholinergic burden (ACB) of different medications are not well known in general population and amongst health care professionals. Our aim is to study the extent of current awareness of ACB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Despite it being well proven and understood in the literature that ACB is linked to poorer outcomes for older patients, awareness appears to remain low in clinical environments. A study conducted in 2020 showed that there is a limited understanding of the potential harms of starting regular anticholinergic medications among clinical staff 18 . Therefore, the process of due pharmacovigilance remains to be embedded into clinical practice among the wider medical team who care for patients above the age of 65 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite it being well proven and understood in the literature that ACB is linked to poorer outcomes for older patients, awareness appears to remain low in clinical environments. A study conducted in 2020 showed that there is a limited understanding of the potential harms of starting regular anticholinergic medications among clinical staff 18 . Therefore, the process of due pharmacovigilance remains to be embedded into clinical practice among the wider medical team who care for patients above the age of 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 2020 showed that there is a limited understanding of the potential harms of starting regular anticholinergic medications among clinical staff. 18 Therefore, the process of due pharmacovigilance remains to be embedded into clinical practice among the wider medical team who care for patients above the age of 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, concomitant use of several medications with anticholinergic action will further increase the likelihood of adverse events [20]. However, a recent survey of pharmacists revealed that 45% of them did not know that these drugs were a risk factor for dementia [65] and only 44% of healthcare professionals knew that cognition was adversely affected by anticholinergics [66].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 2020 showed that there is a limited understanding of the potential harms of starting regular anticholinergic medications among clinical staff. 18 Therefore, the process of due pharmacovigilance remains to be embedded into clinical practice amongst the wider medical team who care for patients above the age of 65.…”
Section: Discussionmentioning
confidence: 99%